Gagasan Perubahan Pasal 42 Peraturan Menteri Dalam Negeri Nomor 65 Tahun 2017 Tentang Pemilihan Kepala Desa Dalam Perspektif Demokrasi Indonesia - Andri Fandio Reza; Dodi Haryono; Gusliana HB (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Villages as the smallest government entity within the state framework were affirmed by theissuance of Law No. 6/2014 on Villages (Village Law). The issuance of the Village Law notonly provides regulatory changes but also provides a paradigm shift regarding the Village,which was originally seen as an extension of the regency or city into an autonomouscommunity unit that has the right and authority to regulate and manage its own territory.Therefore, Article 1 Point 3 of the Village Law mandates the existence of a Villagegovernment organizer, namely led by the Village Head and assisted by Village officialsThis research uses normative legal research. Normative legal research is library legalresearch, namely legal research conducted by making library materials as the main focus.From the results of the research it is concluded that, First, the election of the Village Headfrom the perspective of legal politics is a form of manifestation of democracy at the villagelevel by considering regional autonomy in technical related arrangements by involving thedistrict / city government. Second, the weaknesses of this regulation are quantitative-baseddemocracy or only the highest number of votes, the risk of money politics, the risk ofhorizontal conflict in the community, and conflict due to the determination of the winner ifthe results of the highest number of votes are more than one candidate. The idea ofchanging Article 42 of the Regulation of the Minister of Home Affairs Number 65 of 2017concerning Amendments to the Regulation of the Minister of Home Affairs Number 112concerning Village Head Elections does not have much to do other than rearranging thescheme for determining the winner of the village head election if the number of votes wonis the same.Keywords: Village Head Election, Democracy, Minister of Home Affairs RegulationNo. 65/2017